Maintenance DFMO Increases Survival in High Risk Neuroblastoma - Sholler, Giselle L. Saulnier; Ferguson, William; Bergendahl, Genevieve; Bond, Jeffrey P.; Neville, Kathleen; Eslin, Don; Brown, Valerie; Roberts, William; Wada, Randal K.; Oesterheld, Javier; Mitchell, Deanna; Foley, Jessica; et al. (Scientific reports, 2018)
High risk neuroblastoma (HRNB) accounts for 15% of all pediatric cancer deaths. Despite aggressive therapy approximately half of patients will relapse, typically with only transient responses to second-line therapy. This study evaluated the ornithine decarboxylase inhibitor difluoromethylornithine (DFMO) as maintenance therapy to prevent relapse following completion of standard therapy (Stratum 1) or after salvage therapy for relapsed/refractory disease (Stratum 2). This Phase II single agent, single arm multicenter study enrolled from June 2012 to February 2016. Subjects received 2 years of oral DFMO (750 ± 250 mg/m 2 twice daily). Event free survival (EFS) and overall survival (OS) were determined on an intention-to-treat (ITT) basis. 101 subjects enrolled on Stratum 1 and 100 were eligible for ITT analysis; two-year EFS was 84% (±4%) and OS 97% (±2%). 39 subjects enrolled on Stratum 2, with a two-year EFS of 54% (±8%) and OS 84% (±6%). DFMO was well tolerated. The median survival time is not yet defined for either stratum. DFMO maintenance therapy for HRNB in remission is safe and associated with high EFS and OS. Targeting ODC represents a novel therapeutic mechanism that may provide a new strategy for preventing relapse in children with HRNB.